Geometría: de las ideas del especio al espacio de las ideas - CALVO, Xelo; CARBO, Carme; COLEGIO PUBLICO ANTZUOLA; FARELL, Montse; FORTUNY, Josep M.; GALERA, Pepi; MORA SANCHEZ, J.Antonio; PEREZ GOMEZ, R. (GRAO, 2002)
Otros autores: RUIZ QUILEZ, Jesús; SEGARRA, Lluís